Between human capital and human worth: Popular Valuations of Knowledge in 20th-Century Sweden. Issue 4 (8th August 2019) - Husz, Orsi; Glover, Nikolas
Abstract : This study concerns the history of Swedish public everyday discourse about knowledge and its benefits for the individual, c. 1920–1974. We examine the value(s) ascribed to knowledge – in economic and/or idealistic terms – using private correspondence institutes as our point of departure. These were immensely popular, yet have hitherto been overlooked by historians. First, we argue that commercially driven correspondence education, which was a mass phenomenon in early and mid-20 th -century Sweden, blurred the demarcation lines between general and vocational education, and more importantly between formal and so-called popular education ( folkbildning ). Second, we examine how knowledge and education were promoted and justified in the widely circulated advertisements for Hermods Korrespondensinstitut, the largest of the Swedish correspondence schools. By analysing and contextualizing advertisements over six decades, we find a strong dominance of individualistic economic valuations from the beginning, a successive increase in idealistic valuations over the decades, and an increasing amalgamation of idealistic and economic justifications for knowledge. We argue that the extensive scale of Hermods' and similar institutes' educational activities offers an important key for understanding the social context in which the overall marketization and capitalization of knowledge in the latest decades was able to take root.